2016
DOI: 10.1016/j.dcn.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Social re-orientation and brain development: An expanded and updated view

Abstract: Social development has been the focus of a great deal of neuroscience based research over the past decade. In this review, we focus on providing a framework for understanding how changes in facets of social development may correspond with changes in brain function. We argue that (1) distinct phases of social behavior emerge based on whether the organizing social force is the mother, peer play, peer integration, or romantic intimacy; (2) each phase is marked by a high degree of affect-driven motivation that eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
355
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 359 publications
(377 citation statements)
references
References 177 publications
17
355
3
2
Order By: Relevance
“…For example, emotional experiences related to intimacy, romantic love, jealousy, targeted rejection and acceptance by both partners and peers are often experienced for the first time during adolescence, and the novelty of these experiences may well enhance the impact of the associated emotions (Siegel and Shaughnessy, 1995; Suleiman and Harden, 2016). The important moderating role of the social group in adolescents’ emotional experience is likely to result in behaviors more conducive to norms of a novel peer group than of the natal family unit from which they are preparing to exit (Hostinar et al, 2015; Nelson et al, 2016; Spear, 2000; Steinberg, 2008). Heightened impulsivity, sensation-seeking, and reward sensitivity may help to push adolescents toward seeking novel experiences and social interactions at a time when they are leaving the natal group, establishing their identity, and developing routines in a new setting.…”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, emotional experiences related to intimacy, romantic love, jealousy, targeted rejection and acceptance by both partners and peers are often experienced for the first time during adolescence, and the novelty of these experiences may well enhance the impact of the associated emotions (Siegel and Shaughnessy, 1995; Suleiman and Harden, 2016). The important moderating role of the social group in adolescents’ emotional experience is likely to result in behaviors more conducive to norms of a novel peer group than of the natal family unit from which they are preparing to exit (Hostinar et al, 2015; Nelson et al, 2016; Spear, 2000; Steinberg, 2008). Heightened impulsivity, sensation-seeking, and reward sensitivity may help to push adolescents toward seeking novel experiences and social interactions at a time when they are leaving the natal group, establishing their identity, and developing routines in a new setting.…”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
“…This is most evident in the dual systems and imbalance conceptual models of adolescent neurodevelopment, which both characterize neocortical systems as developing increasing inhibitory control over striatal and limbic regions as adolescence progresses (Casey et al, 2016; Shulman et al, 2016). Even within models that argue for a more complex relationship between top-down and bottom-up neural input across development (Nelson et al, 2016, 2005; Pfeifer and Allen, 2012), the influence of high emotionality on guiding behavior is thought to diminish in part due to maturation of neocortical modulatory inputs. There are many examples where cortically-mediated cognitive processes modulate emotionality in the social domain.…”
Section: Control and Regulation Of Affective Behavior: Form And Fumentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand changes in adolescent motivated behavior these models stress a) the importance of studying brain-connectivity within and between limbic, affective-motivational, and cognitive control brain circuits (Casey, 2015;Casey et al, 2016), b) the influence of social context on observed neural sensitivities (Shulman et al, 2016;Nelson et al, 2016), and c) the importance of pubertal developmental changes and cortical-subcortical flexible interactions (Crone and Dahl, 2012).…”
mentioning
confidence: 99%
“…These studies revolutionized our understanding of adolescent decision making and challenged traditional views that the rise in risky behavior during adolescence occurs because adolescents are irrational or deficient in their decision-making capacities [17]. Rather, adolescents demonstrate unique sensitivity to social and affective contexts, perhaps as a result of the remodeling of the brain during puberty [1819]. Based on developmental cognitive neuroscience research, we now know that the teenage brain is rapidly changing and adapting to its environment.…”
Section: Adolescent Brain Developmentmentioning
confidence: 99%